Adverse drug events in Malaysia: medication-related admissions and pharmacists' experiences - Karuppannan, Mahmathi (2012)
Adverse drug events (ADEs) are a significant cause of patient morbidity and hospital admissions. There are many studies in this area in Western countries. However, little is known about the prevalence and patterns of such events in Malaysia. Health care professionals are in the best position to reduce and prevent adverse drug events. In order to devise preventive strategies based on the prevalence studies, it is important to understand the current practices of health care professionals in this area. This study aimed to determine the different occurrences of ADEs in a Malaysian public hospital as well as the experiences of some Malaysian pharmacists’ of ADEs.